Intranasal administration of butorphanol benefits old patients undergoing H-uvulopalatopharyngoplasty: a randomized trial - Yang, Lin (BMC Anesthesiol, 2015)
BACKGROUND: To evaluate intranasal administration of butorphanol on postoperative pain and early postoperative cognitive dysfunction in old patients undergoing H-uvulopalatopharyngoplasty (H-UPPP). METHODS: A total of 260 male patients (65 to 77 years old) with obstructive sleep apnea hypopnea syndrome and scheduled for H-UPPP were divided randomly to receive intranasal butorphanol, intravenous butorphanol, intranasal fentanyl, or intravenous saline (controls). The definition of preemptive analgesia is that the tested drugs are given before anesthesia induction. Visual analog scale (VAS) and Bruggrmann comfort scale (BCS) scores were recorded at postoperative 1, 6, 12, 18, 24, 36, and 48 h. Postoperative cognitive dysfunction (POCD) was evaluated by Mini-Mental State Examination (MMSE) scores assessed one day before, and 1, 3, and 7 days postsurgery. RESULTS: Compared with control group, those given preemptive analgesia required significantly less sufentanil during surgery, had less pain at postoperative 6–12 h; those given butorphanol experienced less nausea and vomiting, less pain at postoperative 6–24 h, and less POCD. Compared with patients given fentanyl, those given butorphanol required significantly less postoperative fentanyl, had less pain at postoperative 18–24 h, less nausea and vomiting, and less POCD. Compared with patients given intravenous butorphanol, those who received butorphanol by nasal route required significantly less postoperative fentanyl, had less pain at 36 and 48 h, and less POCD. CONCLUSION: Intranasal administration of butorphanol is safe and effective, reducing postoperative usage of analgesics and the incidence of POCD in old patients undergoing H-UPPP. TRIAL REGISTRATION: ChiCTR-TRC-14004121.